Light railways and busways as key driver for sustainable urban development: The Swedish experiences with transit‐oriented development (TOD) - Stojanovski, Todor; Lundström, Mats Johan; Haas, Tigran (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
Sustainable urbanism and good placemaking revolve around creating and maintaining sustainable and attractive places, by reviving planning and urban design paradigms, by experimenting and innovating and by building synergies between the old and the new. The expectations for wide accessibility and networking are very high and the challenge today is to integrate and improve the efficiency and effectiveness of urban and transport systems. The transports have to fulfil the ongoing demands for enhanced efficiency, comfort, safety and speed, as well as the environmental factors in the light of global climate change and energy crisis. One accent in the last 20 years has been on transit‐oriented development (TOD), compact cities and urbanity‐empowering public transports like light railways or light rail transit (LRT) or bus rapid transit (BRT) with its busways as key drivers for sustainable neighbourhoods. TOD in a Swedish (European) perspective is by no means a new idea. Three cases of newer light railway and busway projects (Stockholm, Gothenburg and Norrkoping) are explored in this article and they are seen through a historical overview of the TOD experiences in Sweden and around the world. We also investigate and draw attention to the values of placemaking and sustainable urbanism via the advantages and disadvantages of the urban and regional public transport systems and TOD principles.